2019
DOI: 10.1182/blood-2019-130263
|View full text |Cite
|
Sign up to set email alerts
|

CPX-351 As First Intensive Therapy for Elderly Patients with AML

Abstract: Background Acute myeloid leukemia (AML) in elderly patients is a poor prognosis disease due to many factors that include disease biology, high risk of treatment-related mortality, co-morbid illnesses, geriatric syndromes, and psychosocial factors such as cognitive decline and social isolation. Such factors make it difficult to administer intensive chemotherapy regimens needed to achieve a durable response in older patients with AML. CPX-351, Vyxeos®, is a fixed combination of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Furthermore, in a study of "time trade-off " interviews completed by 200 patients to assess adverse effects on health associated with treatment for AML, CPX-351 induction and consolidation were associated with fewer adverse effects when compared to 7 + 3/5 + 2 [10]. Additionally, in a study of older, newly diagnosed patients with AML treated with CPX-351 (n = 19), FACT-Leukemia scores improved after the first CPX-351 induction compared to baseline in the overall population and in patients achieving CR or CRi [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, in a study of "time trade-off " interviews completed by 200 patients to assess adverse effects on health associated with treatment for AML, CPX-351 induction and consolidation were associated with fewer adverse effects when compared to 7 + 3/5 + 2 [10]. Additionally, in a study of older, newly diagnosed patients with AML treated with CPX-351 (n = 19), FACT-Leukemia scores improved after the first CPX-351 induction compared to baseline in the overall population and in patients achieving CR or CRi [11].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, survival prolongation may result from the receipt of additional therapy, which could also be associated with toxicities and negative impacts on patient qualityof-life. Several prior studies have suggested CPX-351 treatment may provide a quality-of-life benefit over conventional chemotherapy [9][10][11]. However, as data on patient-reported quality-of-life are unavailable in the phase 3 study of CPX-351 versus 7 + 3, it was previously unknown whether the survival benefit conferred with CPX-351 treatment consisted of quality time without toxicities or relapse.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies indicated that the treatment with CPX-351 has the ability to produce quality-of-life benefits compared to conventional chemotherapy [ 42 , 44 , 45 , 46 ].…”
Section: Treatment Toxicitiesmentioning
confidence: 99%
“…With the liposomal encapsulation both drugs can be delivered in a fixed ratio with the highest proportion of synergy to enhance treatment efficacy [67]. CPX-351 preferentially targets leukaemic cells to a greater degree than non-leukaemic cells in the bone marrow, leading to decreased cytotoxicity against normal haematopoietic cells [68]. A small study of CPX-351 as firstline therapy in 30 newly-diagnosed AML patients ≥65 years showed a promising remission rate of 53.2% with a median OS 14.5 months [68].…”
Section: Cpx-315mentioning
confidence: 99%
“…CPX-351 preferentially targets leukaemic cells to a greater degree than non-leukaemic cells in the bone marrow, leading to decreased cytotoxicity against normal haematopoietic cells [68]. A small study of CPX-351 as firstline therapy in 30 newly-diagnosed AML patients ≥65 years showed a promising remission rate of 53.2% with a median OS 14.5 months [68]. In a randomised phase II trial in older adults with untreated AML comparing CPX-351 and conventional '3 + 7' treatment a trend towards increased response rates was observed in the CPX-351 group, 66.7% vs. 51.2%.…”
Section: Cpx-315mentioning
confidence: 99%